2011
DOI: 10.1089/thy.2010.0355
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Serum Thyroglobulin Doubling-Time Under Thyrotropin Suppression in Patients with Papillary Thyroid Carcinoma Who Underwent Total Thyroidectomy

Abstract: Tg-DT (all data or first four data) is a very strong prognostic predictor superior to the classical prognostic factors in patients with PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
163
2
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 226 publications
(178 citation statements)
references
References 18 publications
5
163
2
6
Order By: Relevance
“…• Tg-doubling time (Tg-DT): for the irst time in 2011, Tg-doubling time was proposed as a dynamic prognostic factor [44]. Tg-DT was recognized as an independent prognostic factor for both DFS and CSS of patients, whereas a short Tg-DT time (less than 1 year) is an indicator of poor prognosis.…”
Section: Categories Of Thyroid Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…• Tg-doubling time (Tg-DT): for the irst time in 2011, Tg-doubling time was proposed as a dynamic prognostic factor [44]. Tg-DT was recognized as an independent prognostic factor for both DFS and CSS of patients, whereas a short Tg-DT time (less than 1 year) is an indicator of poor prognosis.…”
Section: Categories Of Thyroid Malignanciesmentioning
confidence: 99%
“…Poorly diferentiated papillary thyroid carcinoma has been discussed as a separate section. Dynamic prognostic factors are based on changes in serum thyroglobulin (Tg) and thyroglobulin antibody (TgAb) after total thyroidectomy, which help with estimation of recurrence and cause-speciic survival (CSS) of PTC patients.• Tg-doubling time (Tg-DT): for the irst time in 2011, Tg-doubling time was proposed as a dynamic prognostic factor [44]. Tg-DT was recognized as an independent prognostic factor for both DFS and CSS of patients, whereas a short Tg-DT time (less than 1 year) is an indicator of poor prognosis.…”
mentioning
confidence: 99%
“…In addition, the trend in basal hsTg, measured when TSH is lowered/suppressed at constant level, should reflect changes in thyroid tissue mass and thus provide a sensitive parameter for disease [19,24,61,65]. This is also supported by a growing number of studies showing the prognostic utility of monitoring the basal hsTg trend and Tg doubling time [66][67][68][69]. A further limitation to the available evidence is that most patients who were enrolled in the studies were affected by low-risk DTC.…”
Section: Clinical Impact Of New Highly Sensitive Tg Assaysmentioning
confidence: 99%
“…Miyauchi et al studied serum Tg kinetics in patients under thyrotropin suppression and demonstrated than Tg-DT less than 1 year under thyrotropin suppression is a very strong predictor of locoregional recurrence [16,17]. Giovanella et al also reviewed Tg-DT under thyrotropin suppression and demonstrated that patients having Tg-DT less than 1 year under thyrotropin suppression significantly improves that chance of positive findings on F-18 FDG PET/CT [10].…”
Section: Resultsmentioning
confidence: 99%